Як визначити рівень професійної компетентності персоналу? - Гуревич, Роман Семенович (НТУ "ХПI", 2011)
The article uncovers the problem of gradation levels of professional competence and the ways of their evaluation. An analysis of foreign and domestic experience is held. The author's approach to determining the level of professional competence and the criteria of formation is taken place. The diagnostic tools for each level of professional competence are considered.
Keywords: компетентність; персонал; критерії оцінки